Underwater Robotics: Surface Cleaning Technics, Adhesion and Locomotion Systems. (21st January 2016) - Albitar, Houssam; Dandan, Kinan; Ananiev, Anani; Kalaykov, Ivan
Underwater robots are being developed for various applications ranging from inspection to maintenance and cleaning of submerged surfaces and constructions. These platforms should be able to travel on these surfaces. Furthermore, these platforms should adapt and reconfigure for underwater environment conditions and should be autonomous. Regarding the adhesion to the surface, they should produce a proper attaching force using a light-weight technics. Taking these facts into consideration, this paper presents a survey of different technologies used for underwater cleaning and the available underwater robotics solutions for the locomotion and the adhesion to surfaces.